Efeitos da derivação gástrica em Y de Roux e da gastrectomia vertical sobre o metabolismo lipídico hepático em ratos obesos - Morita, Fernanda Soares da Silva (2017)
Objective: Here, we compared the effects of Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) on fat liver deposition and expression of hepatic enzymes involved in hepatic de novo (DN) lipogenesis and β-oxidation, in western diet (WD)-obese rats. Background: Bariatric operations are known to improve non-alcoholic fatty liver disease (NAFLD), often found in obese humans. However, comparative studies on the efficacy of different bariatric procedures against NAFLD are scarce. Methods: At two months after WD consumption, the rats were divided into three groups: WD sham operation (WD-Sham), WD-RYGB and WD-SG. Three months after procedures, hepatic steatosis and lipid metabolism were verified. Results: After 3 months, body weight and abdominal fat mass were lower in WD-RYGB, compared with WD-SG rats. Both bariatric operations enhanced glucose tolerance and decreased triglycerides (TG) serum levels. However, total serum cholesterol (CHOL) as well as, hepatic TG and CHOL contents were reduced only in liver of WD-RYGB rats. Hepatic steatosis was corrected in 83% of the WD-RYGB rats, whereas microvesicular steatosis occurred in 100% of the WD-SG livers. Reduction in FASN protein content was observed in both WD-RYGB and WD-SG rats. However, reduced hepatic ACC and enhanced pACC/ACC and CPT-1a protein levels were observed only in WD-RYGB rats. Conclusions: NAFLD is more marked reduced in obese rats that underwent RYGB than SG procedures. This RYGB effect may be associated with decreased hepatic DN lipogenesis, associated with enhancement in β-oxidation, which reduced TG and CHOL content in the liver and serum of WD rats.